EVALUASI PERILAKU SELF CARE MELALUI ASUHAN KEPERAWATAN BERBASIS HOME CARE PADA PASIEN DIABETES MELITUS TIPE 2 DIMASA PANDEMI - Lasmadasari, Novi; Sulastri, Weni (Program Studi Ilmu Keperawatan, Fakultas Ilmu Kesehatan, Universitas Muhammadiyah Bengkulu, 2021)
Physical distancing during a pandemic makes more activities at home, but choosing activities at home must support health, especially for type 2 DM patients who are more at risk of being neglected during the pandemic. The success of managing type 2 diabetes mellitus is largely determined by the patient's ability to behave self-care towards his health status. This study aims to see the self-care behavior of DM patients during physical distancing before and after home care based nursing care was carried out during the pandemic against 15 respondents who were presented descriptively. The results of this study showed an increase in self-care behavior in the good category by 60% after nursing care was carried out. This is evident from several components of self-care that have increased, namely in the behavior of eating patterns (60%), activities/sports (100%), and adherence to medication or taking medication (87%). However, there is a need for further home care and involving the closest people to improve self-care behavior in components of routine blood sugar checks and foot care to prevent complications.Â Keywords: Self-care; DM; Home care.